Soret and Dufour Effects on Steady MHD Natural Convection Flow Past a Semi-Infinite Moving Vertical Plate in a Porous Medium with Viscous Dissipation in the Presence of a Chemical Reaction - Motsa, Sandile; Shateyi, Stanford (IntechOpen, 2011)
None